Evaluation of tangential flow filtration coupled to long-read sequencing for ostreid herpesvirus type 1 genome assembly. Issue 11 (10th November 2022) - Dotto-Maurel, Aurélie; Pelletier, Camille; Morga, Benjamin; Jacquot, Maude; Faury, Nicole; Dégremont, Lionel; Bereszczynki, Maëlis; Delmotte, Jean; Escoubas, Jean-Michel; Chevignon, Germain
Abstract : Whole-genome sequencing is widely used to better understand the transmission dynamics, the evolution and the emergence of new variants of viral pathogens. This can bring crucial information to stakeholders for disease management. Unfortunately, aquatic virus genomes are usually difficult to characterize because most of these viruses cannot be easily propagated in vitro . Developing methodologies for routine genome sequencing of aquatic viruses is timely given the ongoing threat of disease emergence. This is particularly true for pathogenic viruses infecting species of commercial interest that are widely exchanged between production basins or countries. For example, the ostreid herpesvirus type 1 (OsHV-1) is a Herpesvirus widely associated with mass mortality events of juvenile Pacific oyster Crassostrea gigas . Genomes of Herpesviruses are large and complex with long direct and inverted terminal repeats. In addition, OsHV-1 is unculturable. It therefore accumulates several features that make its genome sequencing and assembly challenging. To overcome these difficulties, we developed a tangential flow filtration (TFF) method to enrich OsHV-1 infective particles from infected host tissues. This virus purification allowed us to extract high molecular weight and high-quality viral DNA that was subjected to Illumina short-read and Nanopore long-read sequencing. Dedicated bioinformatic pipelines were developed to assemble complete OsHV-1 genomes with reads from both sequencing technologies. Nanopore sequencing allowed characterization of new structural variations and major viral isomers while having 99, 98 % of nucleotide identity with the Illumina assembled genome. Our study shows that TFF-based purification method, coupled with Nanopore sequencing, is a promising approach to enable in field sequencing of unculturable aquatic DNA virus.